1983
DOI: 10.1111/j.1749-6632.1983.tb35219.x
|View full text |Cite
|
Sign up to set email alerts
|

COVALENT MODIFICATION OF MEMBRANE COMPONENTS IN THE REGULATION OF ERYTHROCYTE SHAPEa

Abstract: Our interest in erythrocyte shape changes originated several years ago when we began to look at some of the functional and structural alterations in erythrocyte membranes that attend the aging cell.' The erythrocyte has a finite lifetime which varies according to species, and the age of the cell at death is somewhat related to the size of the animal; generally, the larger the animal the longer its red cell lifetime.* Reptiles have red cell lifetimes on the order of several hundred days while birds fall into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Studies carried out by Larsen et al [12] in the human erythrocyte, and work carried out in our laboratory using rat erythrocytes, showed that shear promotes Ca2' entry into erythrocytes [ 13,141. As seen in Figure 6, shearing of cells for durations of 5-60 sec promotes hemolysis.…”
Section: Shear Induced Hemolysismentioning
confidence: 75%
See 2 more Smart Citations
“…Studies carried out by Larsen et al [12] in the human erythrocyte, and work carried out in our laboratory using rat erythrocytes, showed that shear promotes Ca2' entry into erythrocytes [ 13,141. As seen in Figure 6, shearing of cells for durations of 5-60 sec promotes hemolysis.…”
Section: Shear Induced Hemolysismentioning
confidence: 75%
“…Transglutaminase (EC 2.3.2. 13), an enzyme that catalyzes the crosslinking of y-glutamyl-elysine bridges [ 1-31, is involved in the covalent modification of proteins [4,5]. In vivo, in the presence of Ca2+ ions, this enzyme catalyses extensive cross-linking of membrane proteins of human [5], rat [6], and mouse [4] erythrocytes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TG2 activation is brought about by elevation of the intracellular concentration of Ca 2+ ions (see Section III and also [52]). In erythrocytes, the entry and exit of Ca 2+ are controlled by ion pumps [53], and the influx is also facilitated by the shear stress on the cells in the circulation [54]. It is not known whether Ca 2+ accumulates in Hb Koln cells as they become energy depleted over their very brief lifespans, lasting only 31 days [16], or whether the cation is delivered in distinct pulses over time.…”
Section: Discussionmentioning
confidence: 99%